Pneumolysin: Pathogenesis and Therapeutic Target - Nishimoto, Andrew T.; Rosch, Jason W.; Tuomanen, Elaine I. (Frontiers in Microbiology, 2020)
Streptococcus pneumoniae is an opportunistic pathogen responsible for widespread illness and is a major global health issue for children, the elderly, and the immunocompromised population. Pneumolysin is a cholesterol-dependent cytolysin (CDC) and key pneumococcal virulence factor involved in all phases of pneumococcal disease, including transmission, colonization, and infection. In this review we cover the biology and cytolytic function of pneumolysin, its contribution to S. pneumoniae pathogenesis, and its known interactions and effects on the host with regard to tissue damage and immune response. Additionally, we review statins as a therapeutic option for CDC toxicity and pneumolysin toxoid as a vaccine candidate in protein-based vaccines.